Promotion and Development of Wushu Sports on College Campuses: Challenges and Opportunities - Xuan Chen (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Wushu is a classic Chinese martial art that is well-known around the world for its aesthetic appeal, physical advantages and rich cultural heritage. In general, wushu is also called as kung-fu. The purpose of this study was to evaluate the opportunities and difficulties associated with wushu sports on college campuses. All collegiate athletes were included in the study's population, and a non-probable, purposeful sample was used. Student-athletes were given a questionnaire created by the researcher. Software called SPSS v.23 was used to analyze the student-athletes' responds. The findings indicate that it is challenging for student-athletes to strike a balance between their engagement in sports and their academic obligations. The wushu players, reported satisfaction with the standard of facilities and equipment, coaching, financial incentives, administrative assistance, and academic success in their particular colleges. The stakeholders may improve the overall experience and performance of wushu players by taking proactive measures to solve the issues raised by using the study's strengths. The growth and promotion of Wushu sports on college campuses are an intersection, where there are obstacles to overcome and prospects for widespread acceptance are uncertain. Colleges can support the global development of Wushu and create a diverse and inclusive sports culture on campuses throughout the globe by solving the challenges that have been highlighted and capitalizing on the possibilities that present themselves.